Ecocritical Consideration: Exploring the Interconnectedness of Nature and Human Experience in Graham Swift’s Tomorrow - Neupane, Ravindra (Curriculum Development Journal, 2024)
The environmental crisis is one of the most tenacious issues of the twenty-first century, and it has never been more relevant than it is right now. This subject, typically associated with the natural sciences, has made its way into literary studies as eco criticism, which provides an intriguing perspective on how place and nature are portrayed in scholarly works. This article aims to adopt an eco critical approach by concentrating on the portrayal of nature, nature-culture relations, and the potential for a noble perspective on the world that is, from the standpoint of the interconnectedness of nature and human experience in Graham Swift’s 2007 novel Tomorrow. The nonhuman characters and the natural world are what give rise to these discussions’ starting points, prompting questions about anthropocentrism, nature’s voice (or lack thereof), and agency. The novel demonstrates a distinctive eco centric orientation in literature while also challenging conventional notions of humanism and drawing attention to current environmental challenges.